P2.110 Risk Factors For Bacterial Vaginosis Among Symptomatic Women Attending STI Clinic in Tel Aviv, Israel. (13th July 2013) - Mor, Z; Shani, A; Dan, M; Shohat, T
Abstract : Background: Bacterial vaginosis (BV) is a common cause for vaginal symptoms and is associated with an increased risk of acquisition of STI/HIV, and with adverse pregnancy outcomes. This study aimed to describe demographic, behavioural and clinical characteristics of symptomatic women diagnosed with BV among those who attended the municipal STI clinic in Tel-Aviv, Israel, and identify risk factors for the disease. Methods: A case-control study, based on data from medical records of women who had attended the clinic between January 2003 and April 2008. Demographic, behavioural and clinical characteristics of symptomatic women diagnosed with BV using the Nugent gramme stain scoring system, were compared to those of symptomatic women who were tested negative for BV. Results: A total of 341 symptomatic women were included in this study, 131 were diagnosed with BV (cases) and 210 were symptomatic but were not diagnosed with BV (control group). In a multivariate analysis BV diagnosis in symptomatic women was related to being born in the former Soviet Union, multiple sexual partners (> 6) in the previous 3 months, and previously infected with HSV or Chlamydia trachomatis . Candida was found to be inversely related to BV diagnosis. Conclusion: BV diagnosis poses a diagnostic challenge for the physician, as the symptoms are not specific even among symptomatic women. Furthermore, candida infection may be characterised with similar clinical symptoms and may delay BV diagnosis. Being familiar with the risk factors for BV may assist the physician in diagnosing the disease in its earlier stage, thus preventing further morbidity. The demographic, behavioural and clinical factors attributed in this study are easily retrieved by anamnesis and can raise the level of suspicion to the possibility of BV.